2012
DOI: 10.1002/tal.1042
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of tall steel buildings by a modified particle swarm algorithm

Abstract: SUMMARY Optimal design of tall buildings, as large‐scale structures, is a rather difficult task. To efficiently achieve this task, the computational performance of the employed standard meta‐heuristic algorithms needs to be improved. One of the most popular meta‐heuristics is particle swarm optimization (PSO) algorithm. The main aim of the present study is to propose a modified PSO (MPSO) algorithm for optimization of tall steel buildings. In order to achieve this purpose, PSO is sequentially utilized in a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Furthermore, PSO is easy to apply and has great computational capacity. In comparison with other optimization approaches, PSO is, however, more efficient and requiring fewer number of function evaluations while gives better or the same quality of results, but it has some weaknesses such as trapping into local optimum in a complex search space and disability to do a good local search around a local optimum (Dimou and Koumousis 2009;Gholizadeh and Fattahi 2014;Gundogdu et al 2015). Optimization function, as the critical attribute of PSO, is very useful to assess the structural damages; however, as shown in Table 11, PSO implementation in SHM is not as much of-GAapplications.…”
Section: Ga Applicationsmentioning
confidence: 99%
“…Furthermore, PSO is easy to apply and has great computational capacity. In comparison with other optimization approaches, PSO is, however, more efficient and requiring fewer number of function evaluations while gives better or the same quality of results, but it has some weaknesses such as trapping into local optimum in a complex search space and disability to do a good local search around a local optimum (Dimou and Koumousis 2009;Gholizadeh and Fattahi 2014;Gundogdu et al 2015). Optimization function, as the critical attribute of PSO, is very useful to assess the structural damages; however, as shown in Table 11, PSO implementation in SHM is not as much of-GAapplications.…”
Section: Ga Applicationsmentioning
confidence: 99%
“…Depending on the optimization purpose, crosssectional areas of the members and/or nodal coordinates separately or simultaneously can be included as the design variables of the problem. Phan et al (2013), Gholizadeh and Fattahi (2014), Gholizadeh and Poorhoseini (2015), Kaveh and Shokohi (2015), Gholizadeh (2015) and Artar (2016) applied some metaheuristic algorithms for the design optimization problems including the sizing variable only. Although it is possible to obtain better results taking into account both sizing and layout variables, in such a case the optimization problem becomes more complex due to rising number of variables (Hasançebi et al 2009;Tang et al 2005;Miguel et al 2013;Silih et al 2010;Deb, Gulati 2001;Dede, Ayvaz 2015;Bekdaş et al 2015;Aydın, Çakır 2015).…”
Section: Introductionmentioning
confidence: 99%
“…() optimized tower structures by using firefly algorithm. Gholizadeh and Fattahi () optimized large‐scale tall steel buildings by a modified particle swarm optimization (PSO) meta‐heuristic algorithm. Their study demonstrated that the modified PSO possesses better computational performance compared with other optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%